Drama Education Differences Between China and Western Countries (Asian Education Studies, 2019)
There are overall differences between the education policies and system between the Chinese and western education systems. These differences are brought up by the differences in government policies, the existing student's and orientation system, the country's population and school size, and community attitudes towards the country’s education system. By contrast, the education policies in western cultures are designed to prepare students to be more successful people in society by gaining enough educational skills and developing a strong friendship. There are several ways in which the Chinese education system completely varies with the western education system. Western countries focus on adopting varieties of learning methods in achieving a democratic government. For the Chinese, there is the management of the massive population, which is managed by a different mode of government. This paper tries to explain the differences between drama education in China and the Western cultures.